The GeFI (Italian Forensic Geneticists) code of conduct. (December 2022) - Buscemi, Loredana; Bini, Carla; Caenazzo, Luciana; De Stefano, Francesco; Domenici, Ranieri; Fattorini, Paolo; Garofano, Paolo; Giardina, Emiliano; Pelotti, Susi; Oldoni, Fabio; Piccinini, Andrea; Robino, Carlo; et al.
Abstract: The Ge.F.I. (Italian Forensic Geneticists) board has set up a working group aimed to develop the "Code of conduct of a Forensic Geneticist". This group includes all practitioners working in the field of forensic genetics. The rules of the code of conduct apply to forensic geneticists belonging to the GeFI group and all of those sharing the GeFI's mission, vision and values applicable to their professional practice, reciprocal relationship and relationship with third parties.